Mega-Gifts: Hijacking Administrative Discretion?. (1st November 2020) - Webb Farley, Kathryn E.; Olejarski, Amanda M.
Abstract : Blending organizational types enables public agencies to seek alternative resources, sometimes yielding mega-gifts large enough to transform the public institution and its agenda. Administrative discretion enables administrators to shape priorities based on negotiations with donors. Drawing on two cases, we examine administrative discretion in negotiating mega-gifts and implementing changes. Two findings suggest that as hybridization increases, trust and confidence in public agencies and actors may erode without responsible use of administrative discretion. First, institutions may pursue change that does not conform to elected officials' goals. Second, absent trusted leaders, institutional actors may mire gifts in institutional cultures that prohibit change.